Takhrij dan Syarah Hadith of Chemical: Prohibition of Blowing Hot Food and Drinks - Sipa Mualipah; Vera Nur Azmi; Soni Setiadji; Medina Chodijah; Muhammad Alfan (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the prohibition of blowing hot food or drinks. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study were that carbonic acid can cause acidosis and alkalosis. The conclusion of this research is takhrij and syarah hadith of the Prophet about the prohibition of blowing hot food or drink by chemical analysis has the opportunity to reveal that blowing hot food or drink can harm the body.